Aplicação e avaliação de um programa de orientação para professores de alunos surdos incluídos - Boscolo, Cibele Cristina (2008)
Currently the Federal Constitution guarantees to everyone to access to school, and then, people with deficiency have the same rights and freedoms than the others. We know that some types of deficiencies exist, however the work in question only approached the deaf people who are in common classroom. This work has been started as general objective to verify the benefits of a program of intervention achieved through with the professors. As specific objective the work tried to analyze school difficulties told by the professors of deaf student in relation to the education of them; to achiev through intervention according to analyses achieved through with the professors to analyze the academic performance of deaf student who belong to the regular classrooms of basic education; to compare the previous analyses with the posterior analyses to the intervention with the professors. For the accomplishment of this study 4 deaf students had been evaluated, of both sexes, carriers of neurossensorial hearind loss who were attending the basic school in regular classrooms of 1st - 4th grades of Municipal Schools, and their respective multipurpose professors. The research was achieved through the techniques of filming, cursivo register, together with a protocol for academic test, behavior and attention of the student, and analysis of the school bulletin. The intervention with professors was achieved through by orientation sessions that had approached subjects that bring doubts in relation to the education of deaf people. After the interventions, the professors and students had been tested again. As conclusion, one observed an improvement in the school performance and socialization of deaf student inrelation to intervention achieved with the professors; this leads to a reflection that the intervention with professors acts directly in deaf student . Programs of intervention must be achieved order to guarantee a better performance of the deaf student, as well as in adjusted socialization to him.